COLOURIMAGERY IN THE HAIKU POEMS OF IMAGISTS POETS - Sharma, Manisha (International Journal of Research -GRANTHAALAYAH, 2014)
Imagism was a movement in early 20th century Anglo-American poetry that favoured precision of imagery and clear, sharp language. Imagists stressed on the direct treatment of the subject matter and strictly adhered to the rule that even a single word was not used unnecessarily. Imagists used the exact word instead of decorative words and rejected most 19th century poetry as cloudy verbosity. Imagist poets were influenced by Japanese Haiku, poems of 17 syllables which usually present only two juxtaposed images. Ezra Pound has made a conscious study of the Japanese Haiku. According to Pound, Japanese make a wonderful use of Haiku where they usually use a single image. A haiku is a haiku because all the images it conveys occur simultaneously in a person’s present perceptions of the world. Ezra Pound is one the major exponents of imagist school who gave systematic theory of modernism. Ezra Pound’s In a Station of the Metro is regarded as a fine specimen of Haiku. Pound recalls that once he stepped out of a "metro", train at La Concorde, and saw suddenly a beautiful face, and then another and another, and then a beautiful child’s face, and then another beautiful woman. Throughout the day, Pound attempted to find words as worthy and as lovely as that sudden emotion. To his mind came an equation which was not in speech but in little sploches of colour. This feeling was the beginning of a language in colourfor Pound. Pound further elaborates that to express this kind of emotion he might find a new school of painting that would speak only by arrangements in colours. To substantiate his arguments, Pound expounds his view in Vorticism.